2011
DOI: 10.1021/jp109905r
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Sparingly Soluble Drug Derivatives of Anthranilic Acid

Abstract: This work is a continuation of our systematic study of the solubility of pharmaceuticals (Pharms). All substances here are derivatives of anthranilic acid, and have an anti-inflammatory direction of action (niflumic acid, flufenamic acid, and diclofenac sodium). The basic thermal properties of pure Pharms, i.e., melting and glass-transition temperatures as well as the enthalpy of melting, have been measured with the differential scanning microcalorimetry technique (DSC). Molar volumes have been calculated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
(74 reference statements)
2
30
1
Order By: Relevance
“…There have been four experimental studies 86,87,89,173 reporting how the solubility of niflumic acid varied with temperature. Surov et al 86 and Perlovich et al 87 both examined the solubility of niflumic acid in hexane and 1-octanol.…”
Section: Auxiliary Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been four experimental studies 86,87,89,173 reporting how the solubility of niflumic acid varied with temperature. Surov et al 86 and Perlovich et al 87 both examined the solubility of niflumic acid in hexane and 1-octanol.…”
Section: Auxiliary Informationmentioning
confidence: 99%
“…Surov et al 86 and Perlovich et al 87 both examined the solubility of niflumic acid in hexane and 1-octanol. Doma nska et al 89 measured niflumic acid solubilities in ethanol and 1-octanol using a dynamic method that recorded the temperature at which the last crystals of the solid solute disappeared. Bustamante et al 173 reported niflumic acid solubilities in ethyl ethanoate and ethanol in the temperature range between 283 and 308 K. The internal consistency of the six datasets was assessed by curve-fitting the measured mole-fraction solubility data to Eq.…”
Section: Auxiliary Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are necessary to describe the thermodynamic solubility. The solubility is not the ideal solubility but is dependent on the solvent [18]. However, the solubility data of many new drugs are often not available in the literature.…”
Section: Introductionmentioning
confidence: 99%